2006
DOI: 10.1152/ajplung.00248.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of macrophage inducible nitric oxide synthase in murine septic lung injury

Abstract: Inducible nitric oxide synthase (iNOS) contributes importantly to septic pulmonary protein leak in mice with septic acute lung injury (ALI). However, the role of alveolar macrophage (AM) iNOS in septic ALI is not known. Thus we assessed the specific effects of AM iNOS in murine septic ALI through selective AM depletion (via intratracheal instillation of clodronate liposomes) and subsequent AM reconstitution (via intratracheal instillation of donor iNOS+/+ or iNOS-/- AM). Sepsis was induced by cecal ligation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
99
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 63 publications
2
99
1
1
Order By: Relevance
“…In this study, we used the model of acid-induced lung injury, a model of aseptic ARDS (2). Similarly to septic lung injury, we found that alveolar macrophages in acid-induced lung injury acquire a classical (M1) activation phenotype in the early phase that is characterized by increased iNOS expression and accumulation of NO metabolites, which are known to contribute to the pathogenesis of ARDS (4,13,(15)(16)(17)(18). Furthermore, we identified the onset of the resolving phase of inflammation, during which suppression of iNOS and predominance of Arg-1, Fizz1, and Ym1 expression, features of M2 polarization, take place.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In this study, we used the model of acid-induced lung injury, a model of aseptic ARDS (2). Similarly to septic lung injury, we found that alveolar macrophages in acid-induced lung injury acquire a classical (M1) activation phenotype in the early phase that is characterized by increased iNOS expression and accumulation of NO metabolites, which are known to contribute to the pathogenesis of ARDS (4,13,(15)(16)(17)(18). Furthermore, we identified the onset of the resolving phase of inflammation, during which suppression of iNOS and predominance of Arg-1, Fizz1, and Ym1 expression, features of M2 polarization, take place.…”
Section: Discussionmentioning
confidence: 94%
“…Most of the studies using animal models examined the role of macrophages in LPS-induced lung injury, a model that resembles septic ARDS (11,18,20). In this study, we used the model of acid-induced lung injury, a model of aseptic ARDS (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding iNOS, there are no studies that correlate it with the operation and with postpneumonectomy pulmonary edema. However, iNOS is related to acute pulmonary lesion and to ARDS (34,35). Since PPPE is considered to be a variant of ARDS, whose triggering factor is the operation, the operation is expected to cause a possible increase in iNOS levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in the lungs of septic murine to have high levels of NO produced by iNOS. [3][4][5][6] NO is also a known regulator of apoptosis and has been shown to inhibit the activity of many caspases both in vivo and in vitro conditions in endotoxin-induced lung injury. 7 High levels of NO can react with superoxide to produce a highly oxidative peroxynitrate.…”
Section: Introductionmentioning
confidence: 99%